Optimizing Ship Management In Narrow Shipping Channels To Reduce The Percentage of Ship Accidents - Reno Aditya Hendriantoro; Capt. Firdaus Sitepu; Dian Junita Arisusanty; I'ie Suwondo (International Journal of Science and Environment (IJSE), 2026)
Indonesian archipelagic waters face increasing shipping accidents in narrow channels due to the growth of ship size, logistics intensity, and hydrodynamic challenges such as bank effect and squat, as reported by the KNKT and the case of MV Tonasa Line XI, with previous studies fragmented between human, operational, and environmental factors without integration of optimization for specific routes such as the Amamapare Channel. This study aims to analyze the optimization of ship maneuvering in narrow channels for safety and efficiency and determine the optimal speed to reduce the risk of collision and grounding. Using a descriptive qualitative approach with a case study design on the MV Meratus Dili during the 2024-2025 voyage in Amamapare, a purposive sample included ship officers namely Master, Chief Officer, Second, and Third Officer based on navigational expertise. Instruments included observation, semi-structured interviews, and documentation, analyzed inductively through data reduction, presentation, and drawing conclusions with triangulation. The results show that speeds >6 knots at low tide reduce Under Keel Clearance (UKC) by 0.35 m; radar and echosounder are crucial, but voyage planning lacks tidal analysis. In conclusion, the optimal speed is 4-5 knots during low tide or high traffic, maintaining a UKC of ≥0.5m; improve SOPs through checklists and training to reduce accidents by 20-30%.